Orthodontic treatment with skeletal anchorage system - Arya Brahmanta; Jusuf Sjamsudin (Dental Journal (Majalah Kedokteran Gigi), 2011)
Background: Correction of class I malocclusion with bimaxillary dental protrusion and unilateral free end right upper ridge in adult patient is one of difficult biomechanical case in orthodontics. Due to this case that needs proper anchorage for upper incisor retraction with missing teeth in the right posterior segment. Purpose: The aim of this study to find an effective therapy for correction of bimaxillary protrusion with unilateral free and ridge. Case: A female patient, 36 year old complaining for the difficulty of lip closure due to severe bimaxillary protrusion with incompetence lip. Case management: Firstly correction of the maxillary and mandibular incisor proclination were done by extraction of the mandibular first premolar, the maxillary second premolar on left side and finally placement of miniplates implant in the zygomatic process on right side as an absolut anchorage. Conclusion: Skeletal anchorage system (SAS) can be considered as an effective therapy for corection of bimaxillary protrusion with unilateral free end ridge.Latar belakang: Koreksi dari maloklusi klas I dari penderita dewasa yang disertai protrusi bimaksiler dengan kehilangan gigi posterior pada regio kanan atas merupakan salah satu kasus sulit untuk dikerjakan terutama berhubungan dengan biomekanik pergerakan giginya dalam perawatan ortodonti. Tujuan: Tujuan dari penulisan artikel ini adalah untuk menemukan terapi yang efektif untuk perbaikan protrusi bimaksiler dan kehilangan gigi posterior pada satu sisi. Kasus: Seorang penderita wanita usia 35 tahun datang dengan keluhan utama kesulitan untuk menutup mulut oleh karena gigi rahang atas dan rahang bawahnya maju dan bibirnya tidak kompeten. Tatalaksana kasus: Koreksi pada gigi insisivus rahang atas dan insisivus rahang bawah yang protrusi dilakukan dengan melakukan pencabutan terlebih dahulu pada gigi premolar pertama dirahang bawah sisi kanan dan sisi kiri serta pencabutan pada gigi premolar kedua di rahang atas sisi kiri dan pemasangan miniplate implant di regio prosesus zigomatikus di sisi kanan sebagai penjangkar absolut. Kesimpulan: Sistem penjangkar absolut pada perawatan ortodonti merupakan pilihan terapi perawatan yang efektif pada kasus penderita dewasa dengan protrusi bimaksiler dan kehilangan gigi posterior pada regio kanan atas.